2019
DOI: 10.1038/s41598-019-45746-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic structure and adaptive positive selection in the Lithuanian population from high-density SNP data

Abstract: The analysis of geographically specific regions and the characterization of fine-scale patterns of genetic diversity may facilitate a much better understanding of the microevolutionary processes affecting local human populations. Here we generated genome-wide high-density SNP genotype data in 425 individuals from six geographical regions in Lithuania and combined our dataset with available ancient and modern data to explore genetic population structure, ancestry components and signatures of natural positive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…The recent Ne was estimated for 50 generations (g), or 1250 years from the present (Table S5). Considering the Lithuanian population, we observed that ancestors of the contemporary Lithuanians first split from Africans in 52,886 YBP, CI (43,394-62,378), and only much later from East Asians-in 27,353 YBP, CI (11,909). The split from Central South and Middle Eastern Asians happened around the same time-in 8278 CI (7354-9201) and in 8895 YBP, CI (6290-11,501), respectively.…”
Section: Reconstructing Past Events Between Ethnolinguistic Regions Omentioning
confidence: 83%
See 2 more Smart Citations
“…The recent Ne was estimated for 50 generations (g), or 1250 years from the present (Table S5). Considering the Lithuanian population, we observed that ancestors of the contemporary Lithuanians first split from Africans in 52,886 YBP, CI (43,394-62,378), and only much later from East Asians-in 27,353 YBP, CI (11,909). The split from Central South and Middle Eastern Asians happened around the same time-in 8278 CI (7354-9201) and in 8895 YBP, CI (6290-11,501), respectively.…”
Section: Reconstructing Past Events Between Ethnolinguistic Regions Omentioning
confidence: 83%
“…People in the different regions of Lithuania seemed to have lived in a relative isolation for a long time because of an inaccessible nature of the terrain. On the landward side, their territory was bounded by the vast forests and swamps, which could have resulted in partial genetic isolation of the Lithuanians, as explained by Urnikyte et al (2019) [11,22,23]. Interestingly, the phylogenetic tree ( Figure 5), which represents the divergence between the ethnolinguistic regions of Lithuania, contradicts the division of the Lithuanian population into two main monophyletic groups (three groups of Žemaitija and three groups of Aukštaitija) on the basis of linguistic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). The TYRP1 locus has been previously identified as a target of selection in Europeans (5,8,9,71,72) although some studies (73,74) have questioned this finding. Our analysis supports the hypothesis of selection at this locus, with a window centered around rs1325132 in the top 0.77% of genome-wide PBS windows on the hunter-gatherer lineage.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the structural deviation causes TMPRSS2 to be less stable, resulting in a reduced overall infection rate that led to reduced CFR in East Asians. We collected and analyzed 221,498 genomes from public databases [19][20][21] and 2,262 whole genomes from the Korean Genome Project 22 . We also traced TMPRSS2 AF distribution in ancient populations by region and time period.…”
Section: Introductionmentioning
confidence: 99%